CHARACTERIZATION OF HIGH-SILICA MORDENITE OBTAINED BY DIRECT SYNTHESIS (Journal of Sciences, Islamic Republic of Iran)
Three high-silica mordenite zeolites differing in SiO440, ratio were prepared by direct synthesis without using any template. The products Si02/A120, ratio is influenced by the starting gel composition. This ratio is increased upon ion-exchange with NH,Cl and subsequent calcination to prepare protonic mordenite. The protonic mordenites with Si02/A1203ra tios of 14.6,29.2 and 34.6 were characterized by X-ray diffraction, energy dispersive X-ray microprobe analysis, scanning electron microscopy and thermogravimetric analysis. Catalytic cracking of n-hexane was studied as a measure of catalytic activity of protonic mordenites. Catalytic activities are expressed as conversion percent of n-hexane. Catalysts with higher Si02/A1,03 were found to be more active